A typical presentation of moxifloxacin-induced DRESS syndrome with pulmonary involvement: a case report and review of the literature - Yinhong Zhang; Xiaoyan Wang; Yang Cheng; Xiaofang Wang; Yunjian Zhang (BMC Pulmonary Medicine, 2022)
Abstract Background Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a kind of hypersensitivity drug reaction involving the skin and multiple internal organ systems. Moxifloxacin has rarely been reported to be a drug that is associated with DRESS syndrome. Lungs are less frequently involved in DRESS syndrome, but their involvements may herald more serious clinical processes. We present a rare typical case of moxifloxacin-induced DRESS syndrome with lungs involved. Valuable clinical data such as changes in the pulmonary imaging and pulmonary function tests was recorded. This case is important for the differential diagnosis of DRESS syndrome with lungs involved by providing clinical manifestations, CT imaging, pulmonary function tests, and biopsy pathological characteristics. The changes in pulmonary imaging and pulmonary function tests may help us understand the mechanism of DRESS syndrome further. Case presentation We report a case of a 47-year-old woman who was treated with oral moxifloxacin for community-acquired pneumonia. The patient subsequently developed a cough, fever, liver injury, skin rash, hematologic abnormalities, and shortness of breath (SOB) followed by pharyngeal herpes and peripheral neuritis. These symptoms, clinical lab index, and CT scan of the lungs improved after the withdrawal of moxifloxacin. The probability of moxifloxacin-induced DRESS syndrome was rated as “Definite”, with 7 scores graded by RegiSCAR. A literature search was also performed with “fluoroquinolones,” “moxifloxacin,” “ciprofloxacin,” “levofloxacin,” “delafloxacin,” and “DRESS” or “drug-induced hypersensitivity syndrome (DIHS)” as the keywords that were put into PubMed. The overall pulmonary involvement was approximately 9.1% (1/11). It is a rare reported case of DRESS syndrome with pulmonary involvement induced by moxifloxacin. We summarized detailed clinical data, including pulmonary imaging and pulmonary function changes. Conclusion This is a rare reported case of DRESS syndrome with pulmonary involvement induced by moxifloxacin. Prompt recognition and correct diagnosis can promote appropriate treatment and accelerate recovery. This case is important for us as a reference in the differential diagnosis of DRESS syndrome and helps us further understand the mechanism of DRESS syndrome.